Rancang Bangun Alat Panen Portabel Sawit Bermotor Menggunakan Flexible Shaft - Oktavianus Ardhian Nugroho; Andreas Reky Kurnia Widhi; Shanti Kumbarasari (Jurnal Penelitian Kelapa Sawit, 2022)
In the world of the plantation industry, to get a maximum harvest, the main factor that needs to be considered is the way of harvesting. An efficient, inexpensive, and effective harvesting process is the main thing that must be achieved. Indonesia as one of the world's palm oil-producing countries together with the Palm Oil Plantation Fund Management Agency (BPDPKS) continues to develop ways to optimize its palm oil production process. The harvesting process today still uses many manual methods using sickles and dodos. Some palm oil harvesting tools are already motorized, however, existing tools still have disadvantages in terms of price and vibration in the shaft. In this article, the author successfully applied the Quality Function Deployment (QFD) method and designed a motorized palm harvester where vibrations from the motor can be reduced by moving the motor's position using a Flexible shaft. Further modifying the gearbox from the material, gear shape, and some elements of the process engine makes the gearbox lightweight and have a small vibration. This study aims to make a motorized palm harvesting tool that can be used to harvest palm fruit quickly and easily. Another thing to aim for is to get a cheap motorized palm oil harvesting machine because all the parts are designed and produced independently and have low vibration. Experiments conducted at the Professional Services Cooperative (KJP) Cipta Prima Sejahtera Banjarmasin obtained a palm oil harvesting machine that had been designed to have a low vibration acceleration value, has easy maintenance, is lighter than existing motorized palm cutting tools, and the speed of cutting branches is many and fast compared to manual dodos cutting tools.